Hubungan Kepatuhan Minum Obat terhadap Penggunaan Terapi Komplementer pada Pasien Hipertensi di Rumah Sakit Umum Mitra Medika Amplas Medan - Afina Muharani Syaftriani; Dedi Dedi; Febrina Febrina (NAJ Nursing Applied Journal, 2025)
Hypertension is a condition in which Systolic Blood Pressure (SBP) is greater than 140 mm Hg and Diastolic Blood Pressure (DBP) is greater than 90 mm Hg. This disease is one of the most common chronic diseases and can affect anyone, both young and old. Hypertension is often called a silent killer because it has no major symptoms, so sufferers are often unaware that they have high blood pressure until serious complications occur. This study aims to determine the relationship between medication adherence and the use of complementary therapies in hypertensive patients at Mitra Medika Amplas Hospital. The research design used an analytical survey method with a cross-sectional approach. The population in this study were all hypertensive patients who received treatment at the internal polyclinic of Mitra Medika Amplas Hospital, with a total population of 1,398 people. The sampling technique used was purposive sampling with the Slovin formula, resulting in 94 respondents. Based on the results of the analysis using the chi-square statistical test, the P-Value was obtained at 0.685 or P-Value > 0.005, which indicates that the alternative hypothesis (Ha) is rejected and the null hypothesis (Ho) is accepted. Thus, it can be concluded that there is no significant relationship between medication adherence and the use of complementary therapy in hypertensive patients at Mitra Medika Amplas Hospital. The conclusion of this study shows statistically that there is no relationship between medication adherence and the use of complementary therapy at Mitra Medika Amplas Hospital this year, which indicates the need for more attention in improving patient adherence to recommended treatment. The conclusion of this study statistically shows that there is no relationship of medication adherence in the use of complementary therapy at Mitra Medika Amplas Hospital.